Issues of Eurasian integration in the parliamentary diplomacy of Armenia - Balasanyan, Grigor (YSU Journal of International Affairs, 2021)
One of the guarantees of the success of any state's foreign policy is the activity of the country's parliamentary diplomacy. Armenia is no exception in this respect. As it is known, Eurasian integration is one of the important directions of Armenia's foreign policy, besides the Republic of Armenia is the founding state of the Eurasian Economic Union along with the Russian Federation, Belarus, and Kazakhstan. But since its inception in 2015, Since January 1, 2009, there has been no Eurasian Integration Committee in the National Assembly of Armenia, which has created a great deal of difficulty in complying with the laws of the Member States of the Union. 2019 The Standing Committee on Regional and Eurasian Integration was set up alongside other committees in the post-revolutionary parliament, which coincided with the presidency of the Republic of Armenia in the EAEU. The article mainly focuses on the annual activity of the Commission itself, as well as on the issues that exist at the legislative level between Member States of the Union.
Keywords: Armenia; EAEU; Integration; Committee; parliament; diplomacy; union; relations